Mechanism of water plugging by dynamic grouting with self-expanding slurry in karst tunnels - Zhan, Shuangqiao; Lu, Lifeng; Liu, Ziyan; Zhou, Jun; Chen, Yuncai; Cao, Lei (Frontiers in Earth Science, 2025)
Clarifying the mechanism of grouting to block karst water outbursts is essential for ensuring effective sealing. This article studies the grouting blocking problem related to the prevention and control of water surge disasters in karst tunnels, focusing on the grouting blocking mechanism of efficiently plugs expanding material (EPEM) under dynamic water conditions. We propose a grouting diffusion formula and blocking criterion that take into account the self-expanding properties of the slurry. First, based on the equilibrium relationship between the friction force and anti-splitting force between the blocking body and the rock wall, we establish an effective blocking condition. Second, by combining capillary theory with Newton’s fluid constitutive equation, we derive the diffusion distance formula for self-expanding slurry under dynamic water conditions. We then construct a mechanical model that uses the length of the critical blocking body as a criterion, revealing the coupling influences of groundwater pressure, grouting pressure, and grouting time. The results indicate that groundwater pressure is positively correlated with grouting pressure and grouting time, while grouting pressure is negatively correlated with grouting time. Finally, we verify the practicality of the proposed criterion through the project at Quanmutang Reservoir in Hunan Province, successfully implementing a parameter combination of 0.5 MPa grouting pressure and 20 min of grouting time to block surge water. This research provides a theoretical basis and engineering guidance for designing water surge grouting in karst tunnels.